CFD modeling of movement of geobag for riverbank erosion control structures - Saman Shabani; Yuntong She; Carlos Frederico Lange (International Journal of Sediment Research)
The erosion of riverbanks led to significant environmental and infrastructure challenges, leading to soil loss, structural damage, and flooding. Since the 1970s, erosion control structures such as geobags have been widely utilized to protect riverbanks. The geobags provide several advantages, including improved durability and cost-efficiency, compared with traditional rip-raps. To design geobags, it is necessary to understand how the geobags will perform under hydraulic loading. Despite numerous fluvial studies focusing on geobag stability, no study examined how a single bag behaves under current loads, and none of the models simulated the motion of bags. This research investigated geobag movement within the channel bed with overset mesh techniques using computational fluid dynamics (CFD). Additionally, an image processing technique was employed to evaluate the borders of the geobags within the channel. By conducting the simulation, the drag and friction forces acting on the single bag were carefully analyzed, and the effects of the shape, fill ratio and material of the geobags were determined. The failure velocity of geobags following the same pattern was determined based on a correlation with the experiment.